Prosodic Focus Effects on Covert "Only" Reading of Scalar Quantifiers in Autistic and Non-autistic Children Under Tonal Language Background. - Jiang, Yuhan; Wang, Ting (Journal of Autism & Developmental Disorders, 2026)
Previous research on prosodic focus comprehension in non-autistic children has yielded inconsistent results, often attributing their difficulties to the presence of the word "only". However, studies on autistic children's understanding of focus are limited and often methodologically rigid. This study builds on previous work by investigating how prosodic focus influences the covert "only" interpretation of scalar quantifiers among Mandarin-speaking children aged 3–8, both autistic and non-autistic, using engaging and dynamic tasks. The present study combined a computer-based Picture-Sentence Judgment and a computer-based Selection Task. Samples included 25 autistic (3 F, 22 M) and 29 non-autistic children (17 F, 12 M) for the judgment task, and 20 autistic (3 F, 17 M) and 25 non-autistic (13 F, 12 M) for the selection task. Results indicated that non-autistic children showed prosodic focus sensitivity, requiring ToM and EF skills but not fully eliciting covert "only" inferences. Prosody enhanced clarity, reducing reliance on advanced reasoning, though vocabulary mattered. Autistic children's comprehension was unaffected by prosody, even with basic ToM and EF skills. Individual traits' influences on their interpretation were minimally affected by focus, highlighting reduced sensitivity. These findings suggest that non-autistic challenges may stem from cognitive capacities, not mere inclusion of "only". Autistic children's diminished sensitivity reflects autism's intrinsic aspects, likely linked to information integration impairments or decreased social motivation.